A novel determination of calcite dissolution kinetics in seawater. (1st December 2015) - Subhas, Adam V.; Rollins, Nick E.; Berelson, William M.; Dong, Sijia; Erez, Jonathan; Adkins, Jess F.
Abstract: We present a novel determination of the dissolution kinetics of inorganic calcite in seawater. We dissolved 13 C -labeled calcite in unlabeled seawater, and traced the evolving δ 13 C composition of the fluid over time to establish dissolution rates. This method provides sensitive determinations of dissolution rate, which we couple with tight constraints on both seawater saturation state and surface area of the dissolving minerals. We have determined dissolution rates for two different abiotic calcite materials and three different grain sizes. Near-equilibrium dissolution rates are highly nonlinear, and are well normalized by geometric surface area, giving an empirical dissolution rate dependence on saturation state (Ω) of: Rate ( g / cm 2 / day ) = 7.2 ± 0.6 · 10 - 4 ( 1 - Ω ) 3.9 ± 0.1 . This result substantiates the non-linear response of calcite dissolution to undersaturation. The bulk dissolution rate constant calculated here is in excellent agreement with those determined in far from equilibrium and dilute solution experiments. Plots of dissolution versus undersaturation indicates the presence of at least two dissolution mechanisms, implying a criticality in the calcite-seawater system. Finally, our new rate determination has implications for modeling of pelagic and seafloor dissolution. Nonlinear dissolution kinetics in a simple 1-D lysocline model indicate a possible transition from kinetic to diffusive control with increasing water depth, and also confirm the importance of respiration-driven dissolution in setting the shape of the calcite lysocline.